2015
DOI: 10.1155/2015/473726
|View full text |Cite
|
Sign up to set email alerts
|

Mild Clinical Behaviour of Crohn Disease in Elderly Patients in a Latin American Country: A Case-Control Study

Abstract: Elderly patients with Crohn disease had a mild clinical course characterized by the lack of escalation to immunosuppressive and anti-tumour necrosis factor therapy, as well as long-term remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…[23] Another study by Yamamoto-Furusho et al found that elderly patients with CD had a mild clinical course characterized by long-term remission and no escalation to immunosuppressive and anti-tumor necrosis factor therapy. [49] Of interest, a cohort analysis of 184 cases in Mexico found that pancolitis, hypoalbuminemia and previous hospitalizations were the strongest predictors of procto-colectomy. [50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Another study by Yamamoto-Furusho et al found that elderly patients with CD had a mild clinical course characterized by long-term remission and no escalation to immunosuppressive and anti-tumor necrosis factor therapy. [49] Of interest, a cohort analysis of 184 cases in Mexico found that pancolitis, hypoalbuminemia and previous hospitalizations were the strongest predictors of procto-colectomy. [50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD.…”
Section: Discussionmentioning
confidence: 99%
“… 8 9 11 14 16 The prevalence of extraintestinal manifestations is also lower, varying from 0% to 7% ( Table 3 ). 8 9 10 11 14 15 16 23 24 25 The frequency of thromboembolic complications, however, is much higher in elderly patients, possibly due to hypercoagulable states, relative immobility, and dehydration associated with illness.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…In elderly patients with CD, most studies have reported a higher female to male ratio, with the proportion of females varying from 47% to 67% ( Table 3 ). 8 9 10 12 24 25 Elderly-onset patients with CD tend to have more rectal bleeding but less abdominal pain, fever, or weight loss at presentation. 2 …”
Section: Diagnostic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strongly agreeing and agreeing responses were combined to represent positive perspectives by the study participants, while strongly disagreeing and disagreeing responses were combined to represent negative perspectives by the participants. All analyses were conducted using IBM SPSS Statistics version 22 [18].…”
Section: Discussionmentioning
confidence: 99%